Public Perception and Hand Hygiene Behavior During COVID-19 Pandemic in Indonesia - Dwipayanti, Ni Made Utami; Lubis, Dinar Saurmauli; Harjana, Ngakan Putu Anom (Frontiers in Public Health, 2021)
Hand hygiene practices are important not only during the corona virus disease 2019 (COVID-19) pandemic, but also critical to prevent the possible spread of other infectious diseases. This study aims to examine the current hand hygiene behaviors during the COVID-19 pandemic, post pandemic behavior intentions, and the relationship between behavior, psychosocial and contextual factors. A cross-sectional online survey survey was conducted from 28 May to 12 June 2020, with 896 valid responses obtained from Indonesian citizens over 18 years old. The survey questions included demographic characteristics, individual practices, risk perceptions, attitude, norm factors and ability factors related to hand hygiene during the COVID-19 pandemic. Descriptive analysis, chi square and multiple logistic regression tests were used to analyse the data. The results showed that 82.32% of female respondents and 73.37% male respondents reported handwashing practice 8 times or more per day during COVID-19 pandemic. Participants who perceived themselves at higher risk of contracting SARS-CoV-2 (OR 7.08, 2.26-22.17), had less negative perception towards the practice (OR 1.93, 1.32-2.82), perceived handwashing as an effective preventive measure (OR 1.77, 1.23-2.54), were female (OR 1.71, 1.21-2.41), perceived a more supportive norm (OR 1.68, 1.15-2.44) and noticed more barriers in access to handwashing facilities (OR 1.57, 1.05 – 2.36) were more likely to engage in hand hygiene practice more frequently during the pandemic. In conclusion, the majority of respondents did increase their frequency of hand hygiene practices during COVID-19 pandemic. In line with previous studies in other pandemic contexts, sex, perceived susceptibility and effectiveness are important predictors of hand hygiene practices, which are similar to findings from previous studies in other pandemic contexts. Addressing social norm related to the perceived hand hygiene practices of friends and important people is a potential health promotion strategy by creating hand hygiene norms in the community.